The Magnetic Casimir Effect between Two Parallel Ferromagnetic Plates - Lien, Do Phuong; Tuan, Nguyen Anh; Anh, Nguyen Tuan (Communications in Physics, 2012)
In this work, we study theoretically the long-range magnetic interaction between two parallel ferromagnetic plates, which arises from the magnetic Casimir effect. The behavior of the interaction is discussed for two configurations when the magnetization is perpendicular or parallel to the plates. The dependence of the Casimir force and Casimir energy on different interplate distances D has been investigated. Results of numerical calculations for a cobalt system have been also presented.